D-Lib Magazine: A Bibliometric Study - Shafi, S. M.; Rather, Rafiq Ahmad; Jan, Rosy; Shah, Gulam Jeelani (Journal of Information and Knowledge, 2007)
This paper examines the articles published in on-line D-Lib magazine for authorship trend, contribution of teaching and professionals, country-wise contribution, degree of collaboration and productivity within different facets of digital /electronic libraries. The study carried out for this paper found that collaborative research is given priority over solo research. The degree of collaboration is found to be 0.66. The study further reveals more contribution from teaching community compared to professionals. Country-wise distribution reveals that most of the contribution comes from the USA and Germany while facet-wise distribution of articles depicts that most of the articles cover digital libraries and preservation followed by metadata /cataloguing.